PENGARUH INDUSTRI PARIWISATA TERHADAP TINGKAT KESEJAHTERAAN MASYARAKAT DI KABUPATEN/KOTA PROVINSI BALI - Aditya Sandi, I Putu Prananda; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
The tourism sector plays an important role in the economy of Bali Province as a job creator for the welfare of the community. The tourism sector, one of which is formed through the trade, hospitality, and restaurant sectors, thus contributes to the welfare of the community. The objectives of this study were (1) to analyze the effect of the number of hotels, the number of restaurants, the number of travel agents, and the number of tourist objects simultaneously on the level of community welfare in the regencies / cities of Bali Province, and (2) to analyze the effect of the number of hotels, the number of restaurants, the number of travel agents, and the number of tourist objects partially against the level of community welfare in the regency / city of Bali Province. The data used is secondary data, namely data on the number of hotels, the number of restaurants, the number of travel agents, the number of tourist objects, and the welfare of the people in the regencies / cities of Bali Province from 2015-2019 so that the number of observations is 45. The analysis technique used is multiple linear regression analysis. The software used is Eviews. The results showed that simultaneously the number of hotels, the number of restaurants, the number of travel agents, and the number of tourist objects had an effect on the level of community welfare in the regency / city of Bali Province. Partially, the number of hotels, the number of restaurants, the number of travel agents, and the number of tourist objects have a positive effect on the level of community welfare in the regency / city of Bali Province. Keywords : Welfare, hotels, restaurants, travel agents, tourism objects